Analysis of Actors' Network and Racial Sentiments in YouTube Commentary (Indonesia U23 VS Guinea U23 Match) - Salla Salika; Adi Bayu Mahadian (Green Publisher Indonesia, 2025)
This article aims to examine the dynamics of YouTube user interaction in the comment column during the football match between the Indonesian U23 National Team and Guinea U23, which took place on May 9, 2024, in Claire Fontaine, Paris. The issue is focused on how comments that appear within the network evoke a sense of ethnocentrism and how key actors influence the spread of racist comments. To approach this problem, a theoretical reference from Social Network Analysis (SNA) is used, which is used to map the network structure and identify the position of actors based on measures of centrality, such as degree, betweenness, closeness, and eigenvector centrality. Data was collected through commentary documentation from the RCTI+ YouTube channel and qualitatively analyzed with the help of @andri_siddhartagautamma and @nido2102, who play a central role in the distribution of information and facilitating the spread of racist comments. The dominant network structure is in the form of a wheel model, which shows the concentration of communication at several key nodes. This study recommends the development of a digital moderation system and the improvement of digital literacy as a strategic step to create a healthier and more inclusive discussion space on social media.